Socialization to Islamic Boarding School Caregivers in the Context of Increasing Community Political Participation in the 2024 Election in Jember Regency - Thamrin, Mohammad; Nusanto , Baktiawan (Universitas Muhammadiyah Jember, 2024)
This article explores the crucial role of students and scholars in Indonesia's socio-political dynamics, with a particular focus on general elections and political empowerment. Santri, as a young generation of intellectuals in Islamic boarding schools, have a great responsibility to actively participate in elections in order to elect leaders with integrity and maintain conduciveness and peace during the election process. Meanwhile, scholars, with their significant influence, play a role not only as spiritual guides but also as agents of change that empower society through political education, enlighten on the importance of healthy political participation, and maintain integrity in the political process. This article also underlines the importance of pesantren as traditional Islamic educational institutions that play a vital role in religious education and active participation in social and political life. In this context, Islamic boarding schools such as the Al Azhar Islamic Boarding School and the Islamic Moral Development Lajnah (LPAI) of Jember Regency also play an important role as activity partners that support community political empowerment with as many as 60 participants from each LPAI recitation every month. Scholars in practical politics often cause debate because of their great influence and dual functions. The presence of ulama is expected to bring coolness, peace, and moral strength in the government. In the context of elections, people often show a decreased enthusiasm to participate, which is caused by a lack of political influence on their lives. Therefore, campaigns are needed to increase the enthusiasm of public participation in the political process. The dynamics of political mobilization based on religious identity are inseparable from the role of religious institutions such as Islamic boarding schools and religious leaders such as kiai. Students, who are educated in Islamic boarding schools, tend to have different lives and views from the general public, often only focusing on religious sciences without being accompanied by general knowledge. With the development of the times, pesantren are also involved in politics, and the role of pesantren in the political process is increasingly visible. Political leaders often approach pesantren for support, demonstrating the importance of pesantren in Indonesia's social and political life. This article emphasizes that the active role of students and scholars is very important in strengthening democracy, maintaining peace, and empowering the community through political education to create justice, welfare, and peace for the Indonesian people